Effect of alkali treatment on the mechanical properties of Poly (lactic acid) / Guineacorn husk particulate bio-composites - Shehu, Umar; Ishiaku, Umaru Semo; Ause, Terver; Mat Taib, Razaina; Aponbiede, Ola (AcademicDirect, 2016)
The paper focuses on the influence of alkali treatment on the mechanical properties of biocomposites made from poly(lactic acid) (PLA) and guineacorn husks particulates (GHP) with respect to that of the untreated (untrd) biocomposites. The composites were prepared using a single screw extruder and an injection moulding machine with particulate compositions varying from 0-40% at 10% interval. It was observed that the tensile strength of the bio-composites decreased with increase in filler content with a maximum value of 31.24MPa at 10% filler content. The tensile modulus recorded an increase with increase in filler content with a maximum value of 2505MPa at 40% filler content while the maximum hardness stood at 72.9HRR at 30% filler content. The alkali treated bio-composites exhibited better properties as compared to those of the untreated ones.